A General Solution of a Generalized Mixed Type of Polynomial Functional Equations - Paokanta, Siriluk; Hengkrawit, Charinthip (Thai Journal of Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE TH <![endif]–> Abstract In this paper, we determine the general solution of the following functional equation … without assuming any regularity condition on the unknown functions … , where … and … are real vector spaces. Keywords: functional equation; Fréchet functional equation; quartic functional equation; additive function; polynomial functional equations <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>